Policy on healthy eating among the population in Uzbekistan - Dadaboyeva Guzal Akbarjonovna (Zien Journals, 2023)
Nutrition and healthy eating program have been one of the crucial component which can prevent the risk of communicable and non-communicable disease among young generation. In this paper some rules and regulations of keeping diet and eating products have been mentioned. One of the important points of the diet is the prohibition to give children in between feedings any food, and first of all various sweets, cookies, buns. This should be paid special attention to the staff and parents.
Keywords: Healthy eating; diet